A protocol for a pilot randomised controlled trial of a Tailored Intervention for people with moderate-to-severe Chronic Obstructive Pulmonary Disease and Co-morbidities delivered by Pharmacists and Consultant respiratory Physicians (TICC-PCP) in Scotland - Richard Lowrie; David Anderson; Aziz Sheikh; Jane Moir; Andrew McPherson; Bethany Stanley; Gillian Cameron; Lynda Attwood; Donald Noble; Elaine Rankine; Jennifer Anderson; Nicola Greenlaw; et al. (Pilot and Feasibility Studies)
Abstract Background Symptomatic chronic obstructive pulmonary disease (COPD) is a global health problem associated with a number of co-morbidities, disproportionately affecting people who are poor. Sub-optimal management of symptomatic COPD and co-morbidities negatively impacts quality of life, ability to work and survival. Previous trials of healthcare professional-led complex interventions have targeted COPD management, but not also simultaneously targeted the treatment of co-morbidities. Recommendations for complex intervention testing include feasibility studies followed by pilot randomised controlled trials (RCTs), including economic and parallel process evaluations. Following a feasibility study, a Tailored, home-based Intervention for people with COPD and Co-morbidities by generalist prescribing Pharmacists collaborating with Consultant respiratory Physicians (TICC PCP) is undergoing pilot testing. The pilot study aims to recruit at least 70% of invited participants within 4 months; deliver TICC PCP to at least 70% of participants in the intervention arm; retain at least 80% of participants (excluding those who died or developed incapacity before the end of the study) until 21-month data collection; and collect at least 90% of in person data at each study time point. In addition, findings from the economic and process evaluations along with information obtained on the proposed quantitative efficacy outcomes inform on the sample size required for a subsequent definitive RCT will help inform on future research. Methods We describe methods for a multicentre pilot RCT, with parallel economic and qualitative process evaluations of TICC PCP. Set in Glasgow and Edinburgh (Scotland), we plan to recruit 100 people with symptomatic COPD and conduct home-based assessments at baseline and at subsequent three monthly follow up visits over a period of 21 months. Independent researchers will collect extensive health and social care data at recruitment (baseline) before participants are randomised (stratified by site and number of respiratory hospitalisations in the past 12 months), to TICC PCP in addition to usual care (UC), or UC alone. Collected data will include objective and subjective measures of health, healthcare utilisation (including prescribing), home circumstances, health related quality of life, healthcare resource use and intervention costs. Follow up data will be collected three monthly for 21 months. The intervention, delivered by NHS Pharmacists visiting participants at home monthly for 6 months, then every 2 months for the next 6 months, involves clinical assessment and intervention at home including prescribing for COPD and co-morbidities. Pharmacists will also assess and help participants to address wider health needs, e.g. appointment attendance and home equipment. Pharmacists will collaborate mainly with consultant respiratory physicians, and General Practitioners. Discussion A holistic, 1 year long, individualised home-based intervention for people with symptomatic COPD and co-morbidities may help address unmet health needs. We will utilise the information obtained from this pilot study, including: the recruitment and retention rates; the sample size required to detect a minimal clinically important difference in the proposed efficacy outcomes of interest; the economic analyses; and process evaluation, to determine whether we should progress to a definitive RCT with parallel process and economic evaluation. Trial registration The trial is registered with the UK Clinical Trials Registry (ISRCTN 43508703).